5G standard : The next generation wireless communication system. Issue 1 (2nd January 2020) - Kumari, Savita; Singh, Brahmjit
Abstract: The telecommunication industry has changed the way we communicate, work and socialize in a remarkable way since its inception. This change is continuous as new services and applications are being developed and deployed worldwide. In order to confront the requirements of new services, there are still many technical challenges. These include enhanced capacity, high data rate, low latency, spectral and energy efficiency. Therefore, researchers target on 5G wireless communication systems that are scheduled to be rolled out by the year 2020. In this paper, we give an overview of the 5G wireless standard and expected performance characteristics. Promising technologies including Millimeter Wave Technology, Massive MIMO, green Communication, and Cognitive Radio Networks are identified to support the requirements of 5G. Finally, we present numerical results on the path loss characteristics utilizing the SUI model for microwave band and modified SUI model for the mm-wave band.